2013
DOI: 10.1021/jo402125u
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Coupling of Phthalimides with Ketones and Aldehydes by Low-Valent Titanium: One-Pot Synthesis of Alkylideneisoindolin-1-ones

Abstract: The reductive coupling of phthalimides with ketones and aldehydes by Zn-TiCl4 in THF gave two- and four-electron reduced products, 3-hydroxy-3-(1-hydroxyalkyl)isoindolin-1-ones and alkylideneisoindolin-1-ones, selectively by controlling the reaction conditions. Therefore, the one-pot synthesis of alkylideneisoindolin-1-ones from phthalimides was effected by this reaction. Although the alkylideneisoindolin-1-ones prepared from phthalimides and aldehydes were formed as mixtures of geometric isomers in most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The change in stability may be caused by a stabilizing ionic–π interaction for the Z -isomer during isomerization [ 61 ]. A similar thermal isomerization towards the more stable isomer induced by catalytic amounts of pyridinium p -toluenesulfonate has been recently reported by Kise and co-workers [ 12 ].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The change in stability may be caused by a stabilizing ionic–π interaction for the Z -isomer during isomerization [ 61 ]. A similar thermal isomerization towards the more stable isomer induced by catalytic amounts of pyridinium p -toluenesulfonate has been recently reported by Kise and co-workers [ 12 ].…”
Section: Resultssupporting
confidence: 81%
“…The simple reaction protocol enabled parallel operations in a Radleys Carousel 6 Plus Reaction Station™. In line with DFT calculations by Kise et al [ 12 ] and independently by Li and Janesko [ 21 ], the thermodynamically favored E -isomer was obtained as the main or sole product. The high E -selectivity was furthermore confirmed by 1 H NMR analyses.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Dehydrations of the photoproducts 3a-e readily furnished the corresponding olefins 4a-e with near complete E-selectivity. Using DFT calculations, Kise et al [26] and independently Li and Janesko [27] showed that the E-isomers of N-substituted 3-arylmethyleneisoindolin-1-ones are thermodynamically more stable than their Z-counterparts. The current results are in line with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al used the same palladium catalyst for the cyclization with phenylglyoxylic acids [23]. Other methods for obtaining isoindolinone alcohols include fluoride-catalyzed nucleophilic additions [24,25], reductive couplings with aldehydes, ketones and olefins [26][27][28][29], and photodecarboxylative additions of carboxylates to phthalimides [30,31].…”
Section: Introductionmentioning
confidence: 99%